Infrared studies combined with hydrogen effusion experiments on nanostructured porous silicon - Koropecki, Roberto Roman (2004)
Nanostructured porous silicon samples prepared by electrochemical anodization of p-type crystalline silicon were exposed to blue light irradiation (k ¼ 400 nm) in air atmosphere. We observed that both photoluminescence and IR spectra evolve during irradiation. We have monitored the evolution of the IR spectra and we have performed effusion experiments to study the photo-oxidation kinetics. Bands located at around 1100 and 900 cm-1 attributed to Si–O related modes are observed to grow with the illumination time, whereas a mode at 910 cm-1 assigned to SiH2 scissoring vibration decreases. The existence of an isosbestic point and the results from factor analysis reveal the presence of only two species evolving in a correlated way. The hydrogen effusion experiments corroborate that the photo-oxidation takes place in a preferential manner, at the expense of hydrogen bonded as dihydride.